Internet connectivity disruption in Iraq (Iraq) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Iraq. Data sourced from IODA.
Network Disruption Incident ID: IQ-2026-0369. Severity: critical. Confidence: 75%